A review on behavior, material properties and finite element simulation of concrete tunnel linings under fire. (August 2022) - Saleheen, Zobaer; Krishnamoorthy, Renga Rao; Nadjai, Ali
Highlights: Tunnel fire characteristics/Fire Curves. Behavior of concrete at elevated temperatures. Thermal properties of concrete at elevated temperature. Mechanical properties of concrete at elevated temperature. Finite element modelling and input parameters for concrete tunnel fire. Abstract: Rigorous understanding of tunnel fire attributes and behavior of concrete at elevated temperatures are indispensable for conducting a numerical simulation of tunnel linings exposed to fire. One of the main feats of tunnel fires is, unlike cellulose fires, temperature of these fires quickly ascends to its zenith, which is higher than conventional cellulose fire temperature. Higher peak temperature in conjunction with rapid heating rate causes spalling in the tunnel linings, which is triggered by excess vapor pressure in concrete pores generated from evaporation of moisture in concrete. Apart from vaporization of moisture, multiple simultaneous physiochemical processes (dehydration/hydration, desorption/sorption, α-β transformation of quartz, decarbonation) take place in concrete when it gets heated. Modelling of a tunnel fire using a commercial finite element tool without taking into account of these physiochemical processes and latent energy associated with the phase changes will result in inaccurate prediction of the results. Thus, the behavior of concrete tunnel liners in extreme fire conditions and relevant material parameters required for numerical simulation are presented in this paper.